Junk Food Consumption as Risk Factor of Poly Cystic Ovarian Syndrome - sompotan, leroy lucano (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2017)
Nowadays, infertile incidences in young married couple are increasing and the women got unreguler menstruation cycles that pretend a Poly Cystic Ovarian Syndrome (PCOS) predisposition. Accretion of PCOS incidences coincide with accretion of junk food (JF) consumption life style in women. This study is description from some literatures of predisposition of JF consumption life style towards PCOS incidence accretion. JF is being PCOS predisposition because its refined carbohydrate increasing insulin resistance risk; high glucose-salts-fats ingredients disturbing hormones balance; JF is processed using partial hydrogenated oil; frying of JF using oxidized oil that producing radical damage of the cell; JF is fried using high temperature over 100Â° celcius that inducing aldehid and keton formation; JF is fried using over 4 times heating. Thus, importance of education about JF consumption and healthy foods in family must be done since the child has born; socialization of JF hazard in the household scale; education of JF consumption and healthy foods in the school; restriction of business permit in JF; restriction and regulation of business advertisement in JF; accretion of business tax in JF; tightening of public regulation about healthy life style.Nowadays, infertile incidences in young married couple are increasing and the women got unreguler menstruation cycles that pretend a Poly Cystic Ovarian Syndrome (PCOS) predisposition. Accretion of PCOS incidences coincide with accretion of junk food (JF) consumption life style in women. This study is description from some literatures of predisposition of JF consumption life style towards PCOS incidence accretion. JF is being PCOS predisposition because its refined carbohydrate increasing insulin resistance risk; high glucose-salts-fats ingredients disturbing hormones balance; JF is processed using partial hydrogenated oil; frying of JF using oxidized oil that producing radical damage of the cell; JF is fried using high temperature over 100Â° celcius that inducing aldehid and keton formation; JF is fried using over 4 times heating. Thus, importance of education about JF consumption and healthy foods in family must be done since the child has born; socialization of JF hazard in the household scale; education of JF consumption and healthy foods in the school; restriction of business permit in JF; restriction and regulation of business advertisement in JF; accretion of business tax in JF; tightening of public regulation about healthy life style.